GSH‐Depleted PtCu3 Nanocages for Chemodynamic‐ Enhanced Sonodynamic Cancer Therapy. (13th November 2019) - Zhong, Xiaoyan; Wang, Xianwen; Cheng, Liang; Tang, Yong'an; Zhan, Guiting; Gong, Fei; Zhang, Rui; Hu, Jun; Liu, Zhuang; Yang, Xiangliang
Abstract: The ultrahigh concentration of glutathione (GSH) inside tumors destroys reactive oxygen species (ROS)‐based therapy, improving the outcome of chemodynamic therapy (CDT)‐enhanced sonodynamic therapy (SDT) by depleting GSH is full of great challenge. Herein, PtCu3 nanocages are first reported as acting as a sonosensitizer with highly efficient ROS generation under ultrasound irradiation. In addition, PtCu3 nanocages can act as horseradish peroxidase‐like nanozymes, catalyzing the decomposition of H2 O2 into OH under acidic conditions for CDT. Surprisingly, PtCu3 nanocages can act as another kind of nanozyme, mimicking glutathione peroxidase (GSH‐Px), which plays an important role in accelerating GSH depletion by oxidizing molecules, further weakening the capacity of tumor cells scavenging ROS by GSH. Both in vitro and in vivo studies demonstrate that PtCu3 nanocages perform well in reducing GSH level for CDT‐enhanced SDT. Moreover, utilizing the high absorption in the near‐infrared region and strong X‐ray attenuation ability, the PtCu3 nanocages are able to conduct photoacoustic/computed tomography dual‐modal imaging‐guided combined cancer therapy. It is worth mentioning that PtCu3 nanocages cause minimal toxicity to normal tissues at therapeutic doses. This work highlights the use of PtCu3 nanocages for effective CDT‐enhanced SDT via GSH depletion. Abstract : This work presents tumor microenvironment‐responsive PtCu3 nanocages for glutathione depletion and chemodynamic therapy enhanced sonodynamic therapy. With their multimodal imaging functions of photoacoustic and computed tomography imaging, PtCu3 nanocages as theranostic agents may pave a new way for imaging‐guided cancer therapy.